PRIVATE AND PUBLIC INTEREST IN THE ‘INTERDICTUM NE QUID IN LOCO PUBLICO FIAT’ - Kamińska, Renata (Zeszyty Prawnicze, 2018)
Roman law accorded a broad scope of protection for public places. Te magistrates responsible for securing it were the curule and plebeian aediles, the censors, and the praetors. Praetors conducted this duty by promulgating interdicts. Ne quid in loco publico fat, which prohibited any activity or installation in a public place which could cause damage, stands out among the other praetorian interdicts. What made it special was that it could be applied both when the potential damage concerned the public interest (utilitas publica), and/or the interest of a private individual (utilitas privata). The damage (damnum) was defned as the loss of a beneft of whatsoever kind the private individual drew from his enjoyment of the public place in question.